2022
DOI: 10.34133/2022/9869510
|View full text |Cite
|
Sign up to set email alerts
|

Precise Design and Deliberate Tuning of Turn-On Fluorescence in Tetraphenylpyrazine-Based Metal−Organic Frameworks

Abstract: The manipulation on turn-on fluorescence in solid state materials attracts increasing interests owing to their widespread applications. Herein we report how the nonradiative pathways of tetraphenylpyrazine (TPP) units in metal−organic frameworks (MOFs) systems could be hindered through a topological design approach. Two MOFs single crystals of different topology were constructed via the solvothermal reaction of a TPP-based 4,4′,4″,4‴-(pyrazine-2,3,5,6-tetrayl) tetrabenzoic acid (H4TCPP) ligand and metal cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…It is worth mentioning that the gradient titrations are accompanied by the red-shift of emission peaks, which are mainly due to the fluorescence resonance energy transfer (FRET), 42 . 43 ) for UIO-66, comparable to or even superior to some reported MOFs 19−21 (Table 1). And the recyclability results in Figure 6d and Figure 7d showed that the detectability of two CoMOFs can be maintained well at least for five cycles.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is worth mentioning that the gradient titrations are accompanied by the red-shift of emission peaks, which are mainly due to the fluorescence resonance energy transfer (FRET), 42 . 43 ) for UIO-66, comparable to or even superior to some reported MOFs 19−21 (Table 1). And the recyclability results in Figure 6d and Figure 7d showed that the detectability of two CoMOFs can be maintained well at least for five cycles.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…As expected, the continuous addition of 3-NT caused the luminescence intensities of three water-stable MOFs to be reduced ceaselessly (Figure a, Figure a, and Figure S19a), with the CIE ranging from (0.19, 0.26) to (0.26, 0.45) for CoMOF-1 (Figure b) and (0.21, 0.22) to (0.26, 0.40) for CoMOF-2 (Figure b). It is worth mentioning that the gradient titrations are accompanied by the red-shift of emission peaks, which are mainly due to the fluorescence resonance energy transfer (FRET), . To reveal the intrinsic relationships between the luminescence intensities of the PBS suspensions of two CoMOFs and UIO-66 and the added 3-NT concentrations, the plots of I 0 / I versus [3-NT] are given in Figure c, Figure c, and Figure S19b (here I 0 and I corresponding to the luminescence intensity of the suspensions of MOFs before and after adding 3-NT).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, overcoming the ACQ effect and introducing the FRET effect by inclusion of photonic guests in MOFs, due to their limited applications and high emissivity in solution, photonic guests exhibit almost quenched luminescence in the solid state when the molecules are aggregated, hence the development of photonic materials has thus been severely constrained by the ACQ effect. 35 As for MOF⊃guests composites, the pore confinement and isolation of guest species within MOFs significantly restricted the intramolecular torsional motion and restrained π−π interactions of guests, thus diminishing the ACQ effect and leading to a significant PLQY enhancement of guests. Another example is that the photonic guests are not stable in air atmosphere or extreme environments, which has severely limited their practical applications.…”
Section: Enhancing Photonic Performancementioning
confidence: 99%
“…In addition to the aforementioned, the synergistic effect between the inherent properties of the individual photonic unit of guests and MOFs, the photonic functionality of MOF⊃guests composites can be further enhanced and optimized due to the fact that the pore microenvironment of MOFs provides an excellent platform for regulating and enhancing the photonic functionality of guest molecules. For instance, overcoming the ACQ effect and introducing the FRET effect by inclusion of photonic guests in MOFs, due to their limited applications and high emissivity in solution, photonic guests exhibit almost quenched luminescence in the solid state when the molecules are aggregated, hence the development of photonic materials has thus been severely constrained by the ACQ effect . As for MOF⊃guests composites, the pore confinement and isolation of guest species within MOFs significantly restricted the intramolecular torsional motion and restrained π–π interactions of guests, thus diminishing the ACQ effect and leading to a significant PLQY enhancement of guests.…”
Section: Enhancing Photonic Performancementioning
confidence: 99%
“…[18,[24][25][26][27] As an excellent luminescent material, metal-organic frameworks (MOFs) have attracted great interest due to their permanent porosity and multiple emission centers. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Such characteristics make MOFs very promising for solid-state photoresponsive materials to address the above issue. First, incorporating photochromic molecules into the pores of MOFs can provide sufficient conformational freedom to achieve efficient photoisomerization.…”
Section: Introductionmentioning
confidence: 99%